Sense of coherence predicts post-myocardial infarction trajectory of leisure time physical activity: a prospective cohort study - Gerber Yariv; Drory Yaacov; Myers Vicki (BMC, 2011)
Abstract Background Physical activity confers a survival advantage after myocardial infarction (MI), yet the majority of post-MI patients are not regularly active. Since sense of coherence (SOC) has been associated with health outcomes and some health behaviours, we investigated whether it plays a role in post-MI physical activity. We examined the predictive role of SOC in the long-term trajectory of leisure time physical activity (LTPA) after MI using a prospective cohort design. Methods A cohort of 643 patients aged ≤ 65 years admitted to hospital in central Israel with incident MI between February 1992 and February 1993 were followed up for 13 years. Socioeconomic, clinical and psychological factors, including SOC, were assessed at baseline, and LTPA was self-reported on 5 separate occasions during follow-up. The predictive role of SOC in long-term trajectory of LTPA was assessed using generalized estimating equations. Results SOC was consistently associated with engagement in LTPA throughout follow-up. Patients in the lowest SOC tertile had almost twice the odds (odds ratio,1.99; 95% confidence interval,1.52-2.60) of decreasing their engagement in LTPA as those in the highest tertile. A strong association remained after controlling for disease severity, depression, sociodemographic and clinical factors. Conclusion Our evidence suggests that SOC predicts LTPA trajectory post-MI. Assessment of SOC can help identify high-risk MI survivors, who may require additional help in following secondary prevention recommendations which can dramatically improve prognosis.